2011
DOI: 10.1186/2191-0855-1-47
|View full text |Cite
|
Sign up to set email alerts
|

Could petroleum biodegradation be a joint achievement of aerobic and anaerobic microrganisms in deep sea reservoirs?

Abstract: Several studies suggest that petroleum biodegradation can be achieved by either aerobic or anaerobic microorganisms, depending on oxygen input or other electron acceptors and appropriate nutrients. Evidence from in vitro experiments with samples of petroleum formation water and oils from Pampo Field indicate that petroleum biodegradation is more likely to be a joint achievement of both aerobic and anaerobic bacterial consortium, refining our previous observations of aerobic degradation. The aerobic consortium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 49 publications
2
18
0
12
Order By: Relevance
“…The same was true for the FdP samples where, despite a general decrease of the Firmicutes group, the Bacilli phylotypes increased especially in the naphthalene cultures. This increase of Bacilli relative abundance is noteworthy, since members of this class have been described as aerobic and anaerobic oil-degrading strains (Van Gestel et al, 2003; da Cruz et al, 2011; Maddela et al, 2016), which suggests a link between the increase of this group and the degradation process.…”
Section: Resultsmentioning
confidence: 87%
“…The same was true for the FdP samples where, despite a general decrease of the Firmicutes group, the Bacilli phylotypes increased especially in the naphthalene cultures. This increase of Bacilli relative abundance is noteworthy, since members of this class have been described as aerobic and anaerobic oil-degrading strains (Van Gestel et al, 2003; da Cruz et al, 2011; Maddela et al, 2016), which suggests a link between the increase of this group and the degradation process.…”
Section: Resultsmentioning
confidence: 87%
“…Recently da Cruz et al (2011) reported evidences from in vitro experiments that petroleum biodegradation could be jointly achieved by aerobic and anaerobic bacterial consortia in biofilms. In their study, an aerobic consortium depleted, in decreasing order, hydrocarbons > hopanes > steranes > tricyclic terpanes, while an anaerobic consortium depleted in the order of hydrocarbons > steranes > hopanes > tricyclic terpanes.…”
Section: Biotransformation Of Petroleum Hydrocarbonsmentioning
confidence: 99%
“…Os microrganismos aeróbios necessitam da presença de oxigênio molecular (condições óxicas) para seu crescimento e para converter os hidrocarbonetos em CO 2 , H 2 O e biomassa. Já os microrganismos facultativos podem crescer na presença (aerobiose) ou ausência (anaerobiose, fermentação) de oxigênio 22,24,25 (condições anóxicas). Os anaeróbios estritos utilizam diferentes aceptores, como nitratos (NO 3-), sulfatos (SO 4…”
Section: Aceptores De Elétrons E Nutrientes Inorgânicosunclassified